Epidemiology of eye disease in the UK: the Bridlington Eye Assessment Project - Poostchi, A. (2023)
Purpose; To determine the prevalence of and impact of eye disease in an elderly population and the diagnostic accuracy of a novel artificial intelligence algorithm for the detection of glaucoma